The state of social protection for agrifood systems workers in West Africa - Gabriela Perin; Jo\~ao Pedro Bregolin Dytz; Lucas Sato; Nourjelha Mohamed Yousif (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
This Working Paper discusses social protection systems and programmes across countries in West Africa, and the extent to which they consider the needs of agrifood system workers. It aims to show how agrifood system workers are included or excluded, the benefits that are relevant to them, and how to improve their access to social protection.
Keywords: 330; agrifood systems; social protection; West Africa